Informática na educação: um recurso para aprendizagem e desenvolvimento profissional de professoras mentoras - Rinaldi, Renata Portela (2006)
This work of research analyzes the contributions and difficulties of a formative process in computer science for the continued formation and professional development of experienced teachers who act as mentors in a Program of Mentoria on-line, linked to the teachers´ doorway in Federal University of Carlos (UFSCar). The methodological dynamics adopted consisted of a research-intervention of collaborative and constructive nature; for involving a double role, it demarcates the necessity to characterize the two moments of the inquiry: the intervention and the research, even if be shown correlated. The intervention had for objectives to promote pedagogical, technical and theoretical knowledge and the use of the TIC's offering the mentors a common repertoire of knowledge on computer science in the education; to introduce the narratives as instrument of reflection about the collective development and individual professional learning; to assist the mentors in their difficulties with the TIC's and to find strategies to solve them; to help them to reflect it about ' what ', ' how ' and ' why ' they made and what they thought besides being sensible to the affective demands which appeared in process. The research had as objective to analyze the processes of learning and professional development involved in the construction of the base of knowledge on computer science in the education, under the perspective of the mentors. Ten experienced teachers with diverse formative and professional trajectories recognized in the area of the education and for the local community as good professionals participated of the research. The instruments of collections of data were: questionnaire, reflexives notes of the mentors and fieldworks produced by the researcher, filmings and on-line interactions. The analysis of the data indicated that the format of the constructed intervention, collaborating and collectively between mentors and researcher, and developed presencially with continuity in the distance evidenced some contributions and difficulties of the undertaken formative process. It still showed that experienced professional, with knowledge, differentiated formation and professional trajectories can interact and share experiences and knowledge that go incorporating procedurally in the search of solutions for real problems integrating the TIC's in their processes of learning and professional development. However, it was necessary to assist the mentors in context of work, value their deriving knowledge and practical of the professional experience and to promote the joint of knowledge with the TIC's, with theories that helped them to encounter, to reflect, and to purify their experiences and subsequently write about them. It was established between researcher/mentors and mentors/mentors a relational base that enabled the construction of a procedural work saw of ' double hand ´ in which the mentors always acted as co-responsible for the elaboration, development and implementation of the formative process.